O PLANEJAMENTO EDUCACIONAL E A CONSTRUÇÃO TEÓRICO-PRÁTICA DA AUTONOMIA DO EDUCADOR - Rosseto, Marisa Ester Aldecôa (2012)
This is a master s degree research that has as a goal to discuss the processes of educational planning and of the continued formation of the teachers of Ensino Médio, involving the aspects of group work from the part of the educators/teachers, the moment of registering, the teaching and pedagogical coordination s knowledge and the construction of the teaching autonomy. This work aims to answer the following questions: Why is it so hard to make the work of planning, the exchange of experience, the group study happen in the school, even when there are paid hours for that? Why isn t the time destined to planning, to the exchange of experience, to the evaluation of the pedagogical work and to the continued formation well enjoyed/taken advantage of in the school? State and municipal government and even many proprietors of private institutions generally put down the educator s throats their projects, not asking for their contribution and the most important, not asking for the involvement on the elaboration process. Are the teachers, when resisting the planning process, reacting to this authoritarian way of initiating politics? If not, what are the reasons that take the teacher to reject the changes in his/her practice? What are the questionings that teachers make considering the planning/plan? The dissertation has as a general objective to analyze the answers presented in the explanatory survey made at the beginning of the research, with four teachers of the same Ensino Medio private school and relate them to the bibliographic studies presented from several authors that study this subject. It still intends to focus on the how teachers can use better the process of the group work to a reflexive movement of the act of educating; on the how much the provided and paid hours can contribute to the discussions about the teaching-learning-evaluating process. As a methodological procedure, besides the initial interview, there was a bibliographic study made on the importance of the word based on Freud s studies and, also, the importance of the multi-referential approach for allowing a plural and more human look on the educational processes. Studies on the concepts attributed to the curricular planning politics: the planning and the teaching plan practices built daily. As results, even if they are temporary, we point to: the documents that were built collectively, in an organized space that was provided by the managers of the school; the construction of memory and authorship, the reflection of practices, the visibility of the work and the pedagogical result. The work still considers the importance of continued formation, planned in paid and guaranteed moments provided by the institution, the importance of the construction of knowledge: teachers and pedagogical coordinator and the history of the practices of registering the plans as inherent aspects to a pedagogical project and that must be recognized, valued and stimulated by the institution s politics.(AU)